The emergence of the Neolithic in North Africa: A new model for the Eastern Maghreb - (:unkn) unknown (My University, 2016)
This paper is focused on cultural and subsistence changes in North African societies during the Early and Middle Holocene, with a special emphasis on the emergence of a productive economy in the Eastern Maghreb. An overview of Western Mediterranean Neolithic spread is first given in order to verify the trajectories evinced in European and North African contexts as well as the different models for neolithisation recently proposed in both contexts. A chrono-stratigraphical, economical and technological analysis carried out from coastal (SHM-1) and inland (Doukanet el Khoutifa and Kef Hamda) Tunisian sites is then proposed. New AMS dates offer insights on Upper Capsian development as well as on the Neolithic transition during the 9th and 8th millennium cal BP. Information gathered at SHM-1 and Kef Hamda indicates the acquisition of some specific Neolithic features such as decorated pottery in a hunter–gatherer context dated to 8000 cal BP. Data from Doukanet el Khoutifa hint at a Neolithic productive economy from 7400 cal BP based on pastoral activities and integrating the consumption of wild animals and plants, with no evidence for agriculture. These data confirm the specific North African pathways identified in other local contexts, where an active role of Epipalaeolithic groups is at the basis of the Neolithic transition through an acculturation process.
Keywords: African Research